2003
DOI: 10.1002/cne.10907
|View full text |Cite
|
Sign up to set email alerts
|

Synapse replacement in the striatum of the adult rat following unilateral cortex ablation

Abstract: Defining the selective pattern of synapse replacement that occurs in different areas of the damaged brain is essential for predicting the limits of functional compensation that can be achieved after various types of brain injury. Here we describe the time course of dendritic reorganization, spine loss and recovery, and synapse replacement in the striatum following a unilateral cortex ablation. We found that the time course for the transient loss and recovery of dendritic spines on medium spiny I (MSI) neurons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…1 or 3 weeks postlesion). After intrastriatal injection of high doses of excitotoxins or after surgical lesioning, HO-1-ir cells were still observed 3 weeks post-lesion, which is consistent with a still active striatal lesion and glial reaction (Akiyama and McGeer, 1989;Marty et al, 1991;Dusart et al, 1991;Rodrigues et al, 2001;McNeil et al, 2003). Furthermore, we observed HO-1-ir in glial cells but we did not find any consistent HO-1 overexpression in striatal neurons.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…1 or 3 weeks postlesion). After intrastriatal injection of high doses of excitotoxins or after surgical lesioning, HO-1-ir cells were still observed 3 weeks post-lesion, which is consistent with a still active striatal lesion and glial reaction (Akiyama and McGeer, 1989;Marty et al, 1991;Dusart et al, 1991;Rodrigues et al, 2001;McNeil et al, 2003). Furthermore, we observed HO-1-ir in glial cells but we did not find any consistent HO-1 overexpression in striatal neurons.…”
Section: Discussionsupporting
confidence: 83%
“…Finally, HO-1 astrocytes observed 1 or 3 weeks after surgical corticostriatal deafferentation may also be related to phagocytic activity. A recent ultrastructural study (McNeil et al, 2003) on the synaptic changes observed in the striatum after unilateral cortical ablation has shown that changes in degenerating corticostriatal terminals occur more slowly than reported for other regions of the brain. Maximal terminal degeneration occurred at 10 days postlesion, and there are still degenerating terminals 30 days post-lesion.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In vitro and in vivo data in rats, indeed, demonstrated that decortication prevents the loss of striatal spines induced by dopamine denervation, thereby suggesting that glutamate is another key determining factor of this pathology (Cheng et al, 1997; McNeill et al, 2003; Deutch et al, 2007; Neely et al, 2007; Garcia et al, 2010). As discussed below, functional interactions between regulating elements of convergent glutamatergic and dopaminergic synapses upon striatal spines, and their impact on the control of intracellular calcium levels, may be critical factors that underlie these functional interactions between glutamatergic and dopaminergic systems to regulate spine pruning and morphology in PD.…”
Section: - Striatal Spine Pathogenesis In Parkinson’s Disease Versumentioning
confidence: 96%
“…Synapse densities around an infarct decline and then recover over time to varying degrees depending on proximity to the infarct core (Brown et al, 2008; Sigler and Murphy, 2010). Remaining projections to denervated regions sprout collateral axons and form new synapses (Cotman and Anderson, 1988; McNeill et al, 2003; Dancause et al, 2005). The axons that most prominently contribute to reinnervation tend to be the most abundant (Raisman and Field, 1990) and the most active (in firing) of the surviving projections (Carmichael and Chesselet, 2002; Carmichael, 2003; Cesa and Strata, 2005; Brus-Ramer et al, 2007).…”
Section: Neural Glial and Vascular Remodeling: Moving Targets For Nmentioning
confidence: 99%